Stany Zjednoczone Europy czy Unia Amerykańska? - Kuź, Michał (Przegląd Politologiczny, 2018)
The paper compares several selected aspects of political culture in the US and in the EU, and presents the fundamental ideas that have led to the emergence of these two federal political bodies, as according to Montesquieu’s typology, both the EU and the US are federal republics. The similarities and differences become even more apparent when comparing the Constitution of the United States and the Lisbon Treaty, which is to constitute the constitutional foundation of the European Union. Such a comparison reveals that the EU and the US are divided by a dialectical difference. This means that these two political constructs apply diametrically opposite solutions to essentially similar political problems. Theoreticians continue to discuss which model of federal republic is better, and whether the EU will have to adopt American solutions, or whether the US will europeanize itself. The author attempts to present the arguments of both sides in this discussion. In his opinion, though, either the EU will experience a breakthrough comparable to the Philadelphia Convention, or will face ultimate disintegration.